2020
DOI: 10.7759/cureus.10119
|View full text |Cite
|
Sign up to set email alerts
|

Coevality of Systemic Lupus Erythematosus With Sickle Cell Trait: A Not So Uncommon Entity

Abstract: The coexistence of systemic lupus erythematosus (SLE) with sickle cell trait is quite sparingly reported in literature. Here, we narrate the case of a 17-year-old girl from Eastern India with sickle cell trait who presented with acute lupus pneumonitis. The challenges to the final diagnosis of SLE with sickle cell trait were because of the often lesser degree of clinical suspicion at the outset. In this report, we discuss this not so uncommon combination of conditions and review related literature. This girl, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…2,9 While the exact mechanisms responsible for these interactions are not fully understood, it is hypothesised that individuals with these interactions may possess an aberrant alternate pathway within their complement system, potentially heightening their vulnerability to autoimmune disease development. 4,9 Another hypothesis posits that individuals afflicted with this condition may have an immune system that does not function optimally. This immune dysfunction may be attributed to factors such as diminished spleen function, disruptions within the complement pathway, and compromised processes of opsonisation and phagocytosis, contributing to the pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,9 While the exact mechanisms responsible for these interactions are not fully understood, it is hypothesised that individuals with these interactions may possess an aberrant alternate pathway within their complement system, potentially heightening their vulnerability to autoimmune disease development. 4,9 Another hypothesis posits that individuals afflicted with this condition may have an immune system that does not function optimally. This immune dysfunction may be attributed to factors such as diminished spleen function, disruptions within the complement pathway, and compromised processes of opsonisation and phagocytosis, contributing to the pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…• susceptible to infections, and potentially prone to autoimmune disorders. 4,9 Patients with SCD may also experience hepatic crises due to red blood cell sickling, leading to hepatomegaly, elevated liver enzyme levels (serum transaminases), or cholestasis. 10 Liver issues in these patients can result from various factors, including hepatic sequestration, viral hepatitis from blood transfusions, haemosiderosis (iron accumulation in the liver), gallstones, or unrelated medical conditions.…”
Section: Articlementioning
confidence: 99%
See 1 more Smart Citation
“…The association of SLE and SCD has been thought to be rare overall; however, several reports document an association 17,18 . For example, a large review of the literature reported on 45 cases of SLE in SCD 19 .…”
Section: Systemic Lupus Erythematosus and Sickle Cell Diseasementioning
confidence: 99%
“…2,15,16 The association of SLE and SCD has been thought to be rare overall; however, several reports document an association. 17,18 For example, a large review of the literature reported on 45 cases of SLE in SCD. 19 One large retrospective study (>350 patients) on SCD patients showed that in a single centre, five cases of SLE were identified.…”
Section: Syste M Ic Lu Pus Ery T H E M Atosus a N D Sick L E Ce L L D...mentioning
confidence: 99%